Exploring intervening influence of interactional justice between procedural justice and job performance: Evidence from South Asian countries - Muhammad Ashraf; Jolita Vveinhardt; Rizwan Raheem Ahmed; Dalia Štreimikienė; Riaz Ahmed Mangi (Amfiteatru Economic Journal, 2018)
The paper investigates the intervening influence of interactional justice between procedural justice and job performance (task, contextual and adaptive performance) of the faculty members of Karachi (Pakistan) and Dhaka (Bangladesh) based government colleges by using Structural Equation Modelling (SEM). Data, for this study, has been collected through pre-designed close-ended questionnaire. The intervening variable fully mediated the relationship between procedural justice and job performance. The result of this study indicates that the performance of government college faculty members can be improved by ensuring fair procedures and dignified treatment of faculty members in the working environment. It can be concluded that teachers can accommodate harsh procedures, subject to courteously and fairly communicated. Significance of this study is that it has investigated the least researched areas in Pakistan and Bangladesh. Its findings can be helpful to the government and college administration while making and implementing policies for college education development in both countries.
Keywords: C4; C12; C13; J14; L2; M14; 330; interactional justice; procedural justice; job performance; college education; faculty motivation